ISLAMIC ECONOMIC IN INDONESIA LAST TEN YEARS (2012-2022); A BIBLIOMETRIC ANALYSIS - Budiyanto, Arief; Sholeh, Achmad Nur; Maulana, Asep Erlan (IJOSMAS, 2023)
This research illustrates the development of the discussion of Islamic economics in Indonesia which is widely discussed by scholars. All of this is summarized through a review of bibliometric analysis carried out in this study. Bibliometrics is a research concept by connecting certain themes in a field to produce reliable and strong indicators. The source used is the MORAREF indexation of the Ministry of Religious Affairs of the Republic of Indonesia. This is expected to be a representation of research themes that discuss Islamic economics. A total of 758 were collected from the page https://moraref.kemenag.go.id and after screening, 415 journals became the basis of the references used. The purpose of this research is to see the trend of Islamic economic research, discussion and areas that are widely researched by scholars in the period 2012-2022. The results of the research findings include: the decline in research related to Islamic economics after 2018 it is an indication that the theme of Islamic economics has experienced saturation. There are eight research clusters from the results of the zakat keyword reference journal network map output that are still quite a lot discussed by experts related to the theme of Islamic economics. The discussion of monetary policy in the scope of Islamic economics is the longest discussed field of discussion while the field of village funds is the latest field discussed by scholars in the scope of Islamic economics.